Microfluidic Fabrication of Hierarchical‐Ordered ZIF‐L(Zn)@Ti3C2Tx Core–Sheath Fibers for High‐Performance Asymmetric Supercapacitors. (29th December 2021) - Wu, Guan; Sun, Suya; Zhu, Xiaolin; Ma, Ziyang; Zhang, Yuman; Bao, Ningzhong
Abstract: We report hierarchical‐ordered ZIF−L(Zn)@Ti3 C2 T x MXene core–sheath fibers, in which a ZIF−L(Zn) nanowall array sheath is grown vertically on an anisotropic Ti3 C2 T x core by Ti−O−Zn/Ti−F−Zn chemical bonds. Through highly efficient microfluidic assembly and microchannel reactions, ZIF−L(Zn)@Ti3 C2 T x exhibits well‐developed micro‐/mesoporosity, ordered ionic pathways, fast interfacial electron conduction and large‐scale fabrication, significantly boosting charges dynamic transport and intercalation. The resultant ZIF−L(Zn)@Ti3 C2 T x fiber presents large capacitance (1700 F cm −3 ) and outstanding rate performance in a 1 M H2 SO4 electrolyte. Additionally, ZIF−L(Zn)@Ti3 C2 T x fiber‐based solid‐state asymmetric supercapacitors deliver high energy density (19.0 mWh cm −3 ), excellent capacitance (854 F cm −3 ), large deformable/wearable capabilities and long‐time cyclic stability (20 000 cycles), which realize natural sunlight‐induced self‐powered applications to drive water level/earthquake alarm devices. Abstract : High‐performance asymmetric supercapacitors based on hierarchical‐ordered ZIF−L(Zn)@Ti3 C2 T x core–sheath fibers have been developed by microfluidic assembly and microchannel reaction methods. Due to an in situ Ti−O−Zn/Ti−F−Zn bonding bridge, well‐developed micro‐/mesoporosity and fast interfacial charge transfer, supercapacitors deliver high energy density, large capacitance, long‐term stability and natural sunlight‐induced self‐powered applications.